Reinvigorating Sustainable Green Economics in Indonesia: Exploring the Nexus between Global Green Economy Index and SDG 8 - Yunita Ratih Wijayanti; Indah Cahyaning Sari (The Journal of Indonesia Sustainable Development Planning, 2024)
This study aims to analyze the relationship between achieving Sustainable Development Goal (SDG) 8 in Indonesia and its related indicators utilized in Global Green Economy Index (GGEI). Through applying a quantitative method by Granger causality test analyzing the time series data of 2000 to 2020, interesting patterns and trends could be observed throughout these years. This research employs the Python libraries pandas, numpy, matplotlib, and statsmodels on the Google Colab platform. The results of the calculations demonstrate that a number of GGEI indicators, including income equality, electricity and heat, manufacturing and construction, green investment attractiveness, biodiversity, oceans, and water stress, are capable of influencing the future value of SDG 8. These findings underscore the crucial necessity for Indonesia's developmental objectives to integrate concepts from the green economy to enhance the realization of SDG 8.